Patellofemoral Cartilage Restoration: Indications, Techniques, and Outcomes of Autologous Chondrocytes Implantation, Matrix-Induced Chondrocyte Implantation, and Particulated Juvenile Allograft Cartilage - Hinckel, Betina B.; Gomoll, Andreas H. (The Journal of Knee Surgery, 2018)
Focal chondral defects are common in the patellofemoral (PF) joint and can significantly impair the quality of life. The autologous chondrocytes implantation (ACI) technique has evolved over the past 20 years: the first-generation technique involves the use of a periosteal patch, the second-generation technique (collagen-cover) uses a type I/III collagen membrane, and the newest third-generation technique seeds and cultivates the collagen membrane with chondrocytes prior to implantation and is referred to as matrix-induced autologous chondrocyte implantation. Particulated juvenile allograft cartilage (PJAC) (DeNovo NT) is minced cartilage allograft from juvenile donors. A thorough physical exam is important, especially for issues affecting the PF joint, to isolate the location and source of pain, and to identify associated pathologies. Imaging studies allow further characterization of the lesions and identification of associated pathologies and alignment. Conservative management should be exhausted before proceeding with surgical treatment. Steps of surgical treatment are diagnostic arthroscopy and biopsy, chondrocytes culture and chondrocyte implantation for the three generations of ACI, and diagnostic arthroscopy and implantation for PJAC. The techniques and their outcomes will be discussed in this article.
Keywords: knee; patellofemoral; patella; trochlear; cartilage; cartilage repair; ACI; MACI; particulated; transplantation; autologous; chondrocytes; cartilage; articular; DeNovo NT